“God please open your fridge!”: Twitter messages to @God in content analysis$dHopes, humor, spirituality, and profanities - Holmberg, Kim (Journal of religion, media and digital culture, 2016)
This study investigates religious communication in social media by analyzing messages sent to God on Twitter. More specifically, the goal of this research is to map and analyze the various contexts in which God is addressed on Twitter, and how the tweets may reflect religious beliefs, ritual functions, and life issues. Using content analysis techniques and phenomenography, tweets addressing God were investigated. The results of this descriptive and indicative study show that religion and religiosity are communicated on Twitter in a manner that creates a unique sphere in which praise and profanities coexist. The tweets in the sample vary a great deal in their content and communicative function, ranging from profanities to prayers and from requests to win the lottery to conversations with and comments about God. Some tweets address God as a form of humour or satire, cursing, or otherwise without any deeper religious intention, while other tweets are apparently genuine messages directed to the transcendent, prayers, with which the senders want to show and share their belief with their followers on Twitter.